Use of Filler Wire for Laser Welding oOf TI-6AL-4V - A. S. H. Kabir (Canadian Institute of Mining, Metallurgy and Petroleum, 2011)
Due to the high specific strength and excellent corrosion resistance, Ti-6A1-4V has been widely applied in aerospace industries. In this study, the welding performance of 3.2-mm and 5.1-mm thick Ti¬6A1-4V sheets was studied using a 4 kW continuous wave Nd: YAG laser. It is found that the use of filler wire, matching the parent metal composition, can bridge the joint gap and produce full penetrated welds up to a width of 0.6 mm without cracking. The laser welds were characterized in terms of the bead geometry, defects, microstructures, and hardness. With increasing joint gap, the percent porosity area increased, reaching just over 1% of the fusion zone area at a gap width of 0.6 mm for the 3.2 mm and 5.1 mm thick sheets. The maximum underfill depth in the Ti-6A1-4V laser welds was about 5% or 7% of the sheet thickness for the 3.2-mm and 5.2-mm thick materials, respectively, meeting the AWS D17-1 specification. The microindentation hardness was maximum in the fusion zone and sharply decreased through the heat affected zone until reaching the base metal value.